Antioxidant Properties in Methanol Extract of Kernels of Commonly Marketed Indian Fruits. Issue 1 (1st January 2021) - Kumar, Indrajeet; Sharma, Rajesh Kumar
ABSTRACT: In the present study, total phenolic and flavonoid contents in the methanol extracts of kernels obtained from the selected fruits such as Mangifera indica, Citrus sinensis, Citrus limetta, Punica granatum, and Carica papaya commonly marketed in India and their antioxidant properties were studied. Total phenolic and flavonoid contents in kernel extracts (measures in mg gallic acid equivalent (GAE)/g fresh weight and mg quercetin equivalent (QE)/g fresh weight, respectively) varied significantly with species ( p <0.05) and ranged between 2.35–7.79 and 0.16–1.17, respectively. Antioxidant activities in kernel extract in terms of 2, 2-Diphenyl-1-picrylhydrazyl, 2, 2ʹ-Azino-bis 3-ethylbenzothiazoline-6-sulfonic acid and ferric reducing antioxidant power (expressed in µM ascorbic acid equivalent (AAE)/g fresh weight) was found maximum in M. indica (102.8, 182.3 and 48.8, respectively) among the tested fruits. Cluster analysis based on biochemical attributes indicated that the kernel of M. indica is biochemically different from other kernels. Thus the present study concludes that the kernel of M. indica should be scaled up for industrial utilization as it possesses significantly higher antioxidant activities as compared to other kernels. Abstract : uf0001